The Orchidaceae of “Parque Municipal de Mucugê”, Bahia, Brazil - Azevedo, Cecilia (Universidad de Costa Rica, 2015)
The Orchidaceae are one of the largest families of flowering plants, with around 20.000 species in approximately 850 genera (Atwood 1986, Dressler 1993). It is well represented in Brazil, with about 2.350 species and 200 genera (Pabst & Dungs 1975, 1977). In Bahia were registered 285 species (Pabst & Dungs 1975, 1977, Harley & Mayo 1980, Harley & Simmons 1986, Toscano-de-Brito 1995, 1998, Toscano-de-Brito & Queiroz 2003).